Quantum dot scanning tunneling microscopy for Majorana bound states in continuum - Zhang, Hai-Rui; Sun, Yong-Ping (Frontiers in Physics, 2022)
We propose a device composed of a quantum dot (QD) connected to a normal metal lead to detect Majorana bound states (MBSs), which are formed at the ends of a topological superconductor nanowire (TSNW) and coupled to the lead with spin-dependent hybridization strengths. The information of the MBSs leaked into the lead is inferred from the spectral function of the QD serving as the tip of a scanning tunneling microscope (STM). It is found that lead–MBSs interaction induces a bound state characterized by an infinitely high peak in the dot’s zero-energy spectral function. The overlap between the two modes of the MBSs turns this bound state into a resonant one, and thus the zero-energy peak is split into three with the height of the central one equaling that in the absence of lead–MBSs coupling. We also find that the MBSs have lower impacts on the additional peak in the dot’s spectral function induced by intradot Coulomb interaction.